Efficacy and safety of bisoprolol compared to other selective beta-1 blockers in the treatment of hypertension: a systematic review and meta-analysis of randomized parallel clinical trials. (14th October 2021) - Jadhav, U; Nair, T; Bansal, S; Ray, S
Abstract: Background: Bisoprolol, a highly cardioselective beta-1 blocker (s-BB) has theoretical advantage over other cardio selective betablockers by way of better potency and tolerability in treating hypertension (HT). Individual published trials comparing s-BB are typically small. Meta-analysis of such trials clarifies the issue and position of bisoprolol in HT therapy. Purpose: This meta-analysis compares bisoprolol with other s-BBs (Atenolol, Betaxolol, Esmolol, Acebutolol, Metoprolol, Nebivolol) for their efficacy and safety in patients with HT. Methods: Literature databases PubMed, Embase, Cochrane Library, Clinicaltrials.gov, Surveillance, Epidemiology and End Results Program and 12 PV databases were searched systematically to identify randomized, parallel clinical trials published from inception to October 2019. Studies which compared bisoprolol with other s-BBs in HT patients were evaluated in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Random effects meta-analyses were conducted to assess mean difference (MD) and 95% confidence interval (95% CI) for blood pressure (BP), heart rate (HR) and lipid profile. Results: 13 studies compared bisoprolol with other s-BBs (metoprolol, atenolol) were included in this meta-analysis. Bisoprolol reported significant reduction in aortic systolic BP [MD: −8.00; 95% CI: −11.57, −4.43; P<0.01] and diastolic BP [MD: −2.90; 95% CI: −4.98, −0.82; P<0.01] during 8 weeks (w) treatment compared to other s-BBs. Bisoprolol treatment for 12w showed significant change in ambulatory heart rate (AHR) [MD: −5.22; 95% CI: −8.37, −2.07; P<0.01], daytime AHR [MD: −5.75; 95% CI: −9.16, 2.34; P<0.01] and nighttime AHR [MD: −3.22; 95% CI: −6.18, −0.26; P=0.03] in comparison to other s-BBs. Significant increase in low frequency HR variability [MD: 100.79; 95% CI: 16.66, 184.91; P=0.02] was reported with bisoprolol treated for 8w compared to other s-BBs. Baroreflex sensitivity significantly favored bisoprolol treated for 8w [MD: 1.01; 95% CI: 0.03, 1.98; P=0.04] in comparison to other s-BBs. HDL-C significantly increased with bisoprolol treated for 52w [MD: 6.80; 95% CI: 3.01, 10.60; P<0.01], 104w [MD: 12.00; 95% CI: 5.04, 18.96; P<0.01] and 156w [MD: 8.00; 95% CI: 0.58, 15.42; P=0.03]. There were no significant changes in total cholesterol [MD: −3.06; P=0.38], LDL-C [MD: −3.60; P=0.18] and triglyceride [MD: −21.00; P=0.26] on treatment with bisoprolol. Serious adverse events did not differ significantly on treatment with bisoprolol compared to other s-BBs. Conclusion: The results of this meta-analysis reveal that bisoprolol showed a significant reduction of BP, HR, baroreflex sensitivity and improved HDL cholesterol levels compared to other s-BBs. Our results highlight the heterogeneity amongst the s-BBs and highlights the benefit of choosing bisoprolol in comparison to other s-BB in the management of HT. FUNDunding Acknowledgement: Type of funding sources: None.